Do late bilinguals access pure morphology during word recognition? A masked-priming study on Hebrew as a second language. Issue 5 (13th June 2018) - FARHY, YAEL; VERÍSSIMO, JOÃO; CLAHSEN, HARALD
Abstract : This study extends research on morphological processing in late bilinguals to a rarely examined language type, Semitic, by reporting results from a masked-priming experiment with 58 non-native, advanced, second-language (L2) speakers of Hebrew in comparison with native (L1) speakers. We took advantage of a case of 'pure morphology' in Hebrew, the so-called binyanim, which represent (essentially arbitrary) morphological classes for verbs. Our results revealed a non-native priming pattern for the L2 group, with root-priming effects restricted to non-finite prime words irrespective of binyanim type. We conclude that root extraction in L2 Hebrew word recognition is less sensitive to both morphological and morphosyntactic cues than in the L1, in line with the Shallow-Structure Hypothesis of L2 processing.